2021
DOI: 10.35784/pe.2021.1.01
|View full text |Cite
|
Sign up to set email alerts
|

COVID-Induced Investor Sentiments and Market Reaction under Extreme Meteorological Conditions: Evidence from Clean Energy Sector of Asia-Pacific

Abstract: The unprecedented global economic and social crisis caused by the coronavirus outbreak has not spared the energy sector. Using a dynamic model, we investigated the effect of COVID-19 cases on investor sentiments and stock returns of clean energy in the Asian-Pacific region. The results show that coronavirus cases negatively affect stock returns using investor sentiments as a transmission channel. We also find a negative effect of air pollution on stock returns. Since COVID-19 restricted trade and plummeted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Thus, it is suggested that likewise US VIX (Sarwar 2012;Dutta 2019), the Chinese VIX is also an investor fear gauge in the Chinese solar energy market. In the short run, enough evidence is available to support the significant effect of investor sentiments on stock returns (Li et al 2017;Yahya et al 2021). Our long-run findings are consistent with You et al (2017) who estimated investor sentiments (measured by Twitter's daily happiness) and stock returns' predictability using quantile regression.…”
Section: Data Analysis and Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, it is suggested that likewise US VIX (Sarwar 2012;Dutta 2019), the Chinese VIX is also an investor fear gauge in the Chinese solar energy market. In the short run, enough evidence is available to support the significant effect of investor sentiments on stock returns (Li et al 2017;Yahya et al 2021). Our long-run findings are consistent with You et al (2017) who estimated investor sentiments (measured by Twitter's daily happiness) and stock returns' predictability using quantile regression.…”
Section: Data Analysis and Discussionsupporting
confidence: 80%
“…during the Covid-19 pandemic (Yahya et al 2021). Compared to metals and exchange rates, solar stocks are more volatile.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our control variables include board size (natural logarithm of total board members), financial leverage (debt to equity ratio), firm age (natural logarithm of firm age in years), firm size (natural logarithm of total assets) and COVID19 (dummy variable, i.e., 1 = year 2020, 0 = otherwise). It is essential to control for the effect of COVID-19 as the Pakistani stock market and industry were trapped by fear, uncertainty, and economic inactivity (Yahya, Shaohua, et al, 2021).…”
Section: A Data and Variablesmentioning
confidence: 99%